1999
DOI: 10.1021/ac981204p
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Particle Separation by Hollow Fiber Flow Field-Flow Fractionation and the Potential Use in Obtaining Particle Size Distribution

Abstract: Particle separation in hollow fiber flow field-flow fractionation (HF-FlFFF) has been greatly improved by experimentation. Flow optimization and the use of an appropriate carrier solution allow for separation of particles by HF-FlFFF to reach nearly the level of separation efficiency normally achieved by a conventional flow FFF system. The retention ratio in HF-FlFFF is confirmed to R ≅ 4λ for a highly retained component. The effect of focusing/relaxation point and the theoretical considerations of particle re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 24 publications
1
55
0
Order By: Relevance
“…4, the lipoprotein fractogram of the sample from a CAD patient showed a clear shift in the peak maximum corresponding to fractionated LDL compared to the fractogram of a healthy donor. By applying the HF FlFFF retention theory [4], the retention time scale can be converted into Stokes' diameter scale (upper horizontal axis in Fig. 4) using the following equation:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4, the lipoprotein fractogram of the sample from a CAD patient showed a clear shift in the peak maximum corresponding to fractionated LDL compared to the fractogram of a healthy donor. By applying the HF FlFFF retention theory [4], the retention time scale can be converted into Stokes' diameter scale (upper horizontal axis in Fig. 4) using the following equation:…”
Section: Methodsmentioning
confidence: 99%
“…In addition, HF FlFFF has recently shown that its separation resolution was comparable to that of rectangular type of FlFFF [4]. Earlier studies of HF FlFFF were focused on the use of HF as a channel for FlFFF [1, 2,11]; the potential of the new technique was enlarged with applications to particles, cells, bacteria, and synthetic organic-soluble polymers [12 -17].…”
Section: Introductionmentioning
confidence: 99%
“…FlFFF systems are available through PostNova Analytics (www.postnova.com), ConSenxus (www.consenxus.com), and Wyatt Technologies (www.wyatt.com). A third configuration that is not commercially available uses a cylindrical tube such as a hollow fiber (HF) membrane [43][44][45] or a ceramic HF [46] (Fig. 2c).…”
Section: Crossflow Fffmentioning
confidence: 99%
“…Due to the tighter control that is enabled, FFF is used in the separation and size characterization of particulates, water-soluble polymers, and biological macromolecules, [6][7][8] and has generated recent interest. 9 In order to maximize the capability and efficiency of the processes described above, it is essential to understand and exploit the relationship between the controllable quantities (such as the wall permeability) and the consequent distribution of particles or solute. For example, tissueengineering bioreactors aim to control cell population growth through nutrient delivery.…”
Section: Introductionmentioning
confidence: 99%